1996
DOI: 10.1021/ac950753h
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Contamination at Silver Surfaces:  Surface Preparation Procedures Evaluated by Raman Spectroscopy and X-ray Photoelectron Spectroscopy

Abstract: The quantity and chemical nature of carbonaceous impurities remaining on polycrystalline Ag surfaces after preparation depend on the protocol used for cleaning. The effectiveness of several preparation protocols was investigated in this study: mechanical polishing with successively finer grades of alumina, Ar + sputtering, chemical polishing, and chemical polishing followed by Tl underpotential deposition. The impurities detected on polycrystalline Ag surfaces subjected to these preparation procedures are carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 31 publications
4
77
0
Order By: Relevance
“…[119] To confound matters further, it has been shown that for silver surfaces prepared by a variety of methods, carbon is always present. [120] There have been attempts to remove contaminants. Norrod and Rowlen have demonstrated that the use of alkanethiols can displace the surface contaminants on SERS-active silver foil, and improve enhancement by a factor of three.…”
Section: à2mentioning
confidence: 99%
“…[119] To confound matters further, it has been shown that for silver surfaces prepared by a variety of methods, carbon is always present. [120] There have been attempts to remove contaminants. Norrod and Rowlen have demonstrated that the use of alkanethiols can displace the surface contaminants on SERS-active silver foil, and improve enhancement by a factor of three.…”
Section: à2mentioning
confidence: 99%
“…As revealed by the measurements, the Raman active species were graphite and nanocrystalline carbon, a typical experience in surface analysis. In the literature, the origin of carbon contamination is discussed in detail [11,12]. One general source of contamination is the metal preparation procedure.…”
Section: Preparationmentioning
confidence: 99%
“…Higher quality rinsing resulted in the disappearance of the carbon Raman bands. The influence of silver surface preparations on carbon contamination have been evaluated by Raman and x-ray photoelectron spectroscopy by Taylor et al 53 The characteristic Raman bands of sp 2 -carbon are also observed in amorphous carbon-hydrogen (a : C-H) films, for instance grown by electric discharge in C 2 H 2 gas. 54 Figure 3(d) gives the time-invariant SERS spectrum assigned by Bjerneld et al 21 to tyrosine (Tyr) adsorbed on 30 nm Ag particles.…”
Section: The Role Of Carbonmentioning
confidence: 99%